Physical simulation of the underclad heat affected zone in a reactor pressure vessel to study intergranular cracking - Cattivelli, Alessandro; Burke, Mary Grace; Dhers, Jean; Francis, John Anthony (Journal of nuclear materials, 2024)
Underclad cracking in nuclear pressure vessels was of significant concern in the 1970s and 1980s before mitigating adjustments were made both to steel compositions and manufacturing practice. Unfortunately, the cracking mechanisms are still not well understood, and this can undermine confidence when changes to cladding operations are under consideration. In this work, Charpy-sized test coupons of 18MND5 steel were subject to a range of thermal cycles that can be experienced by the substrate immediately adjacent to the interface with the overlay. The Charpy test results are considered in combination with analysis of the samples through field emission gun (FEG) scanning electron microscopy (SEM) and wavelength dispersive X-ray spectroscopy (WDXS). The findings suggest that the heat affected zone subject to the coarse grained plus intercritical thermal cycle, before post weld heat treatment, has a peculiar and potentially brittle microstructure. However, in a steel with no obvious macrosegregation, no clear evidence of intergranular cracking in the early stages of the post weld heat treatment could be found. The second part of the work focuses on the effects of segregation regions in large forgings, more specifically ghost lines, on the tendency for underclad cracking. Ghost line regions that subsequently form a coarse grained heat affected zone (CGHAZ), and are then heated to just under the A1 temperature, seem to be the most prone to intergranular cracking. Cracking susceptibility appears to be associated with elevated concentrations of alloying and impurity elements at grain boundaries. •The underclad cracking mechanism in 18MND5 seems different from that in Cr-Mo steels.•Solidification segregation, temper embrittlement appear to cause underclad cracking.•Intergranular fracture risk was highest where prior austenite grain size was highest.•The intercritical heat affected zone had intermediate tendency for fracture.•Deposition strategies should aim at maximum refinement of prior austenite grains.